The rise and demise of the New Public Management: Lessons and opportunities for South East Europe - Wolfgang Drechsler (Central European Public Administration Review)
The essay traces the rise and demise of New Public Management (NPM) during the last quarter of a century, as well as the emergence of a new public administration phenomenon, tentatively called the Neo-Weberian State (NWS), which is argued to be more suitable for coping with the current crisis and its aftermath as well. The essay then focuses on the optimal public administration system for South East Europe, for which the experience of the new Member States of the European Union is used for lesson-drawing. Here, too, it is argued that NPM is definitely not suited for the region, especially in current conditions but also generally. The NWS, in spite of several problems including those of context, remains the current concept of choice in the development of public administration in Europe, and as such can also be utilized in various ways in South East Europe.